Análisis de percepción sobre seguridad turística en el Bosque Protector Guayabillas - Parreño Espinel, Gabriel Sebastián (2022)
The role of security is one of the main interests when Ecuador is shown to the international view, therein lies the relevance of an analysis that nurtures a culture of collective protection and prevents some of the aspects that oppose to the harmony and order proposed in a sustainable society, this analysis must determine alternatives for the oncoming visits within the Bosque Protector Guayabillas. Methodological instruments of descriptive research and field observation were used, in which 17 key factors that affect the perception of security were determined, along with 11 questions to know the perception of security of visitors and 3 observation sheets of the high, middle and lower areas of this urban forest. 10 factors with unsatisfactory or null levels were identified, on which some changes must be proposed to obtain an adequate security management, such as: lack of training and preparation of law enforcement officers\; as well as a large percentage of visitors with fear of being robbed according to the surveys. It was found that the cooperation between the community, the police and private security should be synergistic and constant, and must promote some changes in the BPG Master Management Plan, which has not received any changes since 2001.